Olfactory dysfunction in COVID-19 pandemic and its long-term outcome - Krishna Jadvani; Siddharth Badola (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Olfactory dysfunction (OD) has commonly affected covid infected patients. This study is done to detect, analyse and study the recovery pattern of OD in laboratory confirmed COVID-19 infected patients since there is very less data available on OD recovery rate. Methods: Study design is a prospective cohort type and patients were followed up over 16 months of duration. Data was collected of COVID-19 positive patients from January 2020 to May 2021 who were hospitalized and seen after discharge in out-patient department of tertiary care Santosh medical college and hospital, Ghaziabad (Delhi NCR). In these patients, university of Pennsylvania smell identification test (UPSIT)-40 was used for assessment of OD. Results: Total number of patients enrolled in the study were 153 of which 15 were lost to follow-up. None of the patients died. Among the 138 hospitalized patients with RTPCR-confirmed COVID-19 infection [mean (SD) age, 38.91 (13.90) years; 70 males (50.7%); 68 females (49.3%)]. This is a prospective cohort study studied over 16 months. At the time of diagnosis of COVID-19, smell sensation was categorised based on UPSIT test as anosmic in 69.6% of the patients, severely amosmic in 9.4%, moderately anosmic in 12.3%, mildly anosmic in 8.7%. After a follow-up for 16 months, full recovery was observed in 125 patients (90.6%). Conclusions: Prognosis for recovery of olfaction dysfunction in COVID-19 patients was favourable. Individuals with sudden onset and gradual onset OD had higher rate of recovery over one-month follow-up period. Sudden onset OD had higher rate of recovery than gradual onset.